A representação do negro em Leite derramado, de Chico Buarque - Glauciane Aparecida dos Santos (2017)
This study aims to reflect about the representation of Black characters in the novel Leite Derramado by Chico Buarque. It also aims to take into consideration in the analysis the point of view of Eulálio Montenegro dAssumpção, a centenary senior from a broke aristocratic family, who narrates through his memories the his familys saga. It is through his perspective that many important moments in the Brazilian history will be shown in the narrative. We will investigate how these memories are important to the comprehension of ethnic-racial discourse in Brazilian literature. This research has the purpose of ressignifying the discursive and ideological conditions of Black characters presented in the novel and questioning their constitution as subjectsin the novel. To achieve this goal we propose to reflect about the Racial Democracy Myth, the Sociology of Racial Relations and the concepts of Identity, Cordiality of Brazilian man, Symbolic Violence, Whiteness and the relation between memory and history.